Graphene Embedded with Transition Metals for Capturing Carbon Dioxide: Gas Detection Study Using QM Methods - Mollaamin, Fatemeh; Monajjemi, Majid (MDPI AG, 2023)
Carbon dioxide (CO2) adsorption on decorated graphene (GR) sheets with transition metals (TMs) including iron, nickel and zinc was investigated for removing this hazardous gas from the environment. TM-doped GR results in higher activity toward gas detecting than pristine graphene nanosheets. TM embedding restrains hydrogen evolution on the C sites, leaving more available sites for a CO2 decrease. The Langmuir adsorption model with ONIOM using CAM-B3LYP functional and LANL2DZ and 6-31+G (d,p) basis sets due to Gaussian 16 revision C.01 program on the complexes of CO2→(Fe, Ni, Zn) embedded on the GR was accomplished. The changes of charge density illustrated a more considerable charge transfer for Zn-embedded GR. The thermodynamic results from IR spectroscopy indicated that ΔGads,CO2→Zn@C−GRo has the notable gap of Gibbs free energy adsorption with a dipole moment which defines the alterations between the Gibbs free energy of the initial compounds (ΔGCO2 o and ΔGZn@C−GRo) and product compound (ΔGCO2→Zn@C−GRo) through polarizability. Frontier molecular orbital and band energy gaps accompanying some chemical reactivity parameters represented the behavior of molecular electrical transport of the (Fe, Ni, Zn) embedding of GR for the adsorption of CO2 gas molecules. Our results have provided a favorable understanding of the interaction between TM-embedded graphene nanosheets and CO2.
Keywords: CO2; graphene nanosheet; Environmental engineering; (Fe, Ni, Zn); environmental pollutant; TA170-171; graphene nanosheet; gas sensor; CO2; (Fe, Ni, Zn); environmental pollutant; Langmuir adsorption; DFT; Langmuir adsorption; Environmental technology. Sanitary engineering; TD1-1066; gas sensor; 7. Clean energy